2021
DOI: 10.1038/s41598-021-82099-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sagging breasts and other risk factors associated with mastalgia: a case–control study

Abstract: The aim of this study is to compare patients with and without mastalgia and to analyze the factors affecting mastalgia and its severity. The patient’s age, height, weight, educational status, marital status, and occupation were recorded in all subjects. In addition, the women were asked about the presence of any risk factors for mastalgia, such as tea and coffee consumption, smoking, alcohol consumption, and weight gain. The sternal notch to nipple distance (SNND) was measured to determine whether there was br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Most of our respondents did not have family history of breast disease (84.45%). Similar observations were found in some previous study by Jahdi et al 2 and Çomçalý et al 16 showed majority of their respondents were housewife 2 , unemployed 16 , married 2,15,16 and multiparous 2,15,16 .…”
Section: Discussionsupporting
confidence: 91%
“…Most of our respondents did not have family history of breast disease (84.45%). Similar observations were found in some previous study by Jahdi et al 2 and Çomçalý et al 16 showed majority of their respondents were housewife 2 , unemployed 16 , married 2,15,16 and multiparous 2,15,16 .…”
Section: Discussionsupporting
confidence: 91%
“…Breasts, especially larger breasts, tend to sag when a bra is not worn for a long time, due to the extensive stretch of soft tissues and ligaments [9]. Breast separation and ptosis may lead to health problems such as mastalgia [10], shoulder and back pain [11], and posture alteration due to the downward pull of breasts [12]. Dissatisfaction with one's appearance can lead to mental issues such as body-related anxiety and a sense of inferiority [13].…”
Section: Introductionmentioning
confidence: 99%